The rationality of de-radicalization efforts for the children of terrorists at Al-Hidayah Islamic Boarding School - Harahap, Husnul Isa; Irmayani, T.; Lubis, Fuad Hasan (Penerbit Universiti Kebangsaan Malaysia, 2019)
Al-Hidayah Islamic Boarding School was established in 2016 in Sei Mencirim Village, Kutalimbaru Sub-District, Deli Serdang District in Sumatera. Since then it has attracted some attention from the Muslim community as it teaches the deradicalization subject and other subjects to its students who are the children of terrorists. The aim of this paper is to examine the rationality behind the deradicalization efforts taking place at the school. This study refers to some of the theories on radicalism and terrorism presented by Mark Juergensmeyer (2001), Mia Bloom (2007), Daniel Koehler (2016) and Hafal Ahmad (2017). This study uses the quantitative research methodology to gather the needed data for its findings or results. Among the findings are the de-radicalization process for the children of terrorists is a rational effort. The participation of former terrorists in the program is also a rational choice. However, there are some important aspects to be reviewed and improved by the school in order to maintain and achieve the planned goals or aims for the school. Firstly, it is necessary to strengthen the teachers’ quality and quantity in the teaching the subjects offered by the school. Secondly, the design and implementation of the de-radicalization subject and other subjects need to be measured and tested regularly covering the contents of the subjects and their teaching aids. Thirdly, it is necessary to set indicators that can be used to measure the progress and success of the school from time to time.